2014
DOI: 10.1111/jcal.12062
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of ineffective cooperative learning teams

Abstract: Cooperative learning has many pedagogical benefits. However, if the cooperative learning teams become ineffective, these benefits are lost. Accordingly, this study developed a computer-aided assessment method for identifying ineffective teams at their early stage of dysfunction by using the Mahalanobis distance metric to examine the difference between the sequential test scores of the unknown team and the test scores of a reference group of functioning teams. The effectiveness of the proposed method was verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…(Note that the MD values are provided in the 14th column of the dataset.) In addition, various procedures have been proposed for identifying ineffective teams at an early stage of their development (Hsiung, Luo & Chung, ). Importantly, the proposed techniques complement traditional survey‐based methods and provide a viable basis for the development of computer‐aided solutions for monitoring and assessing team functioning (Hsiung et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…(Note that the MD values are provided in the 14th column of the dataset.) In addition, various procedures have been proposed for identifying ineffective teams at an early stage of their development (Hsiung, Luo & Chung, ). Importantly, the proposed techniques complement traditional survey‐based methods and provide a viable basis for the development of computer‐aided solutions for monitoring and assessing team functioning (Hsiung et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…This consists of the quick identification of early warning signals and a rapid response to prevent a problem escalating. This is based on studies on crisis management and team development which emphasize the importance of the early recognition of unwanted developments and early warning signs of conflict . In the program, this is operationalized by the team in a meeting at which they formulate indicators of the early warning signs of rigidity.…”
Section: Premises Of the Programmentioning
confidence: 99%
“…It starts with phase 1 in which the team members, on the basis of their team goals, define their team questionnaire covering their indicators of flexibility. Monitoring these indicators in phase II by repeated use of the questionnaire supports the recognition of early signs of rigidity . The reports are input for team meetings in which the members reflect on the insights and feedback.…”
Section: The Program In Nine Stepsmentioning
confidence: 99%
“…While the overwhelming body of literature supporting Cooperative Learning as a framework is positive (Johnson & Johnson, 1994;Slavin, 1980Slavin, , 1989Slavin, , 1996Slavin, , 1999Slavin, , 2012, deeper analyses paint a more nuanced picture of the conditions that must be met to realize positive benefits through this approach. Without a carefully monitored and implemented approach, learning teams can become ineffective and outcomes suffer as a result (Hsiung, 2014, Golub & Buchs, 2014. For example, Hsuing's (2014) study of cooperative grouping in undergraduate engineering courses found that teams can become ineffective at any stage of the learning process, and require careful monitoring.…”
Section: Hundreds Of Studies Have Been Conducted Since the 1970s On Tmentioning
confidence: 99%
“…The graph of the mean benchmark scores over time at each school (See Figure 1) reveals interesting trends that support the SBSA results, as well as my sense, as a frequent observer and instructional coach, of more student-centered cooperative learning happening at School 2. The literature on maximizing the efficacy of cooperative learning emphasized that teachers ought to make deep initial investment in group structures and strategies (Hsiung, 2014, Golub & Buchs, 2014. Mrs. B started the school year with great focus on cooperative strategies and emphasized students learning cooperative routines.…”
Section: Interpretationsmentioning
confidence: 99%